Determination of optical parameters of CdTe films by principal angle ellypsometry - Kornienko, K.N.; Odarych, V.A.; Poperenko, L.V.; Vuichik, N.V. (Functional Materials, 2006)
The principal angle and ellipticity of the light wave reflected from the surface of the single-crystal silicon coated by a CdTe film have been measured in 366-579 nm spectral region. Using a specially developed computer graphic program of the ellipsometric data processing optical constants and a film thickness distribution over the sample surface area have been determined. The CdTe refraction index values obtained for the film are considerably lower than that of CdTe single crystal. That is explained by porous structure of the film. В спектральнiй областi 366-579 нм вимiряно головний кут i елiптичнiсть свiтлової хвилi, вiдбитої вiд поверхнi монокристалiчного кремнiю, вкритою плiвкою телуриду кадмiю. Представлено комп'ютерну графiчну програму обробки елiпсометричних вимiрiв, з допомогою якої знайдено оптичнi сталi та розподiл товщини плiвки по площi зразка. Oдержанi значення показника заломлення плiвки телуриду кадмiю значно меншi за показники заломлення монокристалiчного СdTe, що пояснюється пухкою структурою плiвки. В спектральной области 366-579 нм измерены главный угол и эллиптичность световой волны, отраженной от поверхности монокристалического кремния, покрытой пленкой теллурида кадмия. Представлена компьютерная графическая программа обработки эллипсометрических измерений, с помощью которой найдены оптические постоянные и распределение толщины пленки по площади образца. Полученные значения показателя преломления пленки теллурида кадмия значительно меньше показателя преломления монокристалического СdTe, что объясняется рыхлой структурой пленки.